Effects of TSH inhibition after total thyroidectomy on Tg, VEGF, TSGF, CD44V6, sIL-2R and T lymphocyte subsets in patients with differentiated thyroid carcinoma - Li-Dan Zhang (Journal of Hainan Medical University, 2018)
Objective: To study the effects of TSH inhibition after total thyroidectomy on Tg, VEGF, TSGF, CD44V6, sIL-2R and T lymphocyte subsets in patients with differentiated thyroid carcinoma (DTC). Methods: A total of 100 patients with DTC in our hospital from January 2014 to January 2017 were enrolled in this study. The subjects were divided into the control group (n=50) and the treatment group (n=50) randomly. The control group was treated with thyroid hormone replacement therapy, the treatment group was treated with levothyroxine sodium oral therapy, the two groups were treated for 1 week. The serum Tg, VEGF, TSGF, CD44V6, sIL-2R and peripheral blood CD3+, CD4+, CD8+ of the two groups before and after treatment were compared. Results: There were no significant differences of the serum Tg, VEGF, TSGF, CD44V6, sIL-2R of the two groups before treatment. The serum Tg, VEGF, TSGF, CD44V6, sIL-2R of the two groups after treatment were significantly lower than before treatment, and that of the treatment group after treatment were significantly lower than the control group. There were no significantly differences of the peripheral blood CD3+, CD4+, CD8+ of the two groups before treatment. The peripheral blood CD3+, CD4+ of the two groups after treatment were significantly higher than before treatment, the peripheral blood CD8+ of the two groups after treatment were significantly lower than before treatment, and that of the treatment group after treatment were significantly better than the control group. Conclusion: TSH inhibition after total thyroidectomy for patients with DTC can reduce the serum Tg, VEGF, TSGF, CD44V6, sIL-2R levels, improve the cellular immunity function, and it was worthy clinical application.